2021
DOI: 10.1039/d1dt00110h
|View full text |Cite
|
Sign up to set email alerts
|

Site-selective protonation of the one-electron reduced cofactor in [FeFe]-hydrogenase

Abstract: Hydrogenases are bidirectional redox enzymes that catalyze hydrogen turnover in archaea, bacteria, and algae. While all types of hydrogenase show H2 oxidation activity, [FeFe]-hydrogenases are excellent H2 evolution catalysts as...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 62 publications
2
25
0
Order By: Relevance
“…67 In a recent study, we addressed the influence of pH on the accumulation of reduced H-cluster states under turnover conditions. 55 We noted a clear trend for Hred to dominate at pH < 7 and Hred′ to dominate at pH > 7, confirming former observations. 54 This can explain the bell-shaped activity distribution as a function of pH: the preference for Hred under proton-rich conditions might indicate that the H-cluster forms an unready, H 2 -inhibited geometry upon PCET to the Fe−Fe cofactor, e.g., controlled by the low pK a of the glutamic acid residues in the PT pathway.…”
Section: Understanding [Fefe]-hydrogenase Catalysissupporting
confidence: 90%
“…67 In a recent study, we addressed the influence of pH on the accumulation of reduced H-cluster states under turnover conditions. 55 We noted a clear trend for Hred to dominate at pH < 7 and Hred′ to dominate at pH > 7, confirming former observations. 54 This can explain the bell-shaped activity distribution as a function of pH: the preference for Hred under proton-rich conditions might indicate that the H-cluster forms an unready, H 2 -inhibited geometry upon PCET to the Fe−Fe cofactor, e.g., controlled by the low pK a of the glutamic acid residues in the PT pathway.…”
Section: Understanding [Fefe]-hydrogenase Catalysissupporting
confidence: 90%
“…Both 1e – -reduced states H red′ and H red are formed upon proton-coupled electron transfer and can be distinguished in FTIR spectroelectrochemistry due to their different p K a values Figure compares two difference spectra recorded in potential-jump experiments at (a) pH 9 and (b) 5 . Under alkaline conditions and reducing potentials (−650 mV vs SHE), H ox converts exclusively into H red′ .…”
Section: Complementary In Situ Approachesmentioning
confidence: 99%
“…128 Figure 15 compares two difference spectra recorded in potential-jump experiments at (a) pH 9 and (b) 5. 129 Under alkaline conditions and reducing potentials (−650 mV vs SHE), H ox converts exclusively into H red′ . On the opposite, H red converts exclusively into H sred under acidic conditions and strongly reducing potentials (−750 mV vs SHE).…”
Section: Complementary In Situ Approachesmentioning
confidence: 99%
“…S3). [16] While [FeFe]-hydrogenases prepared at pH 4 have been shown to adopt HoxH as main oxidized resting state in the presence of NaDT [20][21][22] , we now found that HoxH is not observed at pH 4 when CrHydA1 was mixed with TCEP, DTT, ascorbic acid, or no reductant (Fig. S2A).…”
Section: Resultsmentioning
confidence: 60%